Aqueous Solid Electrolyte Interphases in Water‐in‐Salt Electrolytes and Beyond - Radhika Krishna Hema; Alberto Varzi (ChemElectroChem)
The key issue with advancing aqueous batteries is the narrow electrochemical stability window (ESW) of the electrolyte; past efforts have focused on extending the water decomposition limits, principally using the highly concentrated water‐in‐salt electrolytes (WiSEs) with limited “free” water. However, the high salt content largely complicates practicability and long‐term performance, necessitating alternative strategies to enhance ESWs without relying entirely on huge amounts of salt. Forming stable, functional interphases on electrode surfaces can help realize this vision by masking the electrode from water, thereby inducing high overpotentials for hydrolysis. Solid electrolyte interphase (SEI) formation on the negative electrode has been observed to be particularly tricky to navigate through, due to the faster kinetics of water reduction or the hydrogen evolution reaction (HER), something popularly termed the “cathodic challenge.” We aim, through this concept review, to deliver a comprehensive overview of the mechanistic and electrochemical understandings that have been recognized over the years about the SEI formation in aqueous electrolytes. A broad analysis is drawn ranging from diluted to highly concentrated systems (WiSEs), while highlighting current challenges and limitations. The discussion is kept limited to Li‐based batteries, which however, in most cases, could also be extrapolated to Na and K‐based ones.